Implantação do PCP em uma microempresa do vestuário fitness - Frost, Viviane Cristina Arzani (2024)
The production function has been examined since the origin of humanity. It can be defined as a set of activities that lead to the transformation of a tangible good into another with more excellent utility. Throughout history, production techniques have been improving, and with the Industrial Revolution, some requirements emerged, such as the organization of production, standardization of products, and production processes. This led to the development of new techniques and systems to organize, plan, and control production. With the advance of globalization, competitiveness also increased, and overcoming the ever-growing competition became a challenge to stay in the market. Nevertheless, consumers began to have greater demands regarding the delivery time of the finished product, price, personalized service, and, especially, quality. Thus, a company that is prepared against its competitors will gain new market shares. To meet these demands, planning and controlling production are essential processes; therefore, companies rely on a tool or department called Production Planning and Control (PPC), which aims to create plans that will guide production and serve as a guide for its control. Production planning and control determine what will be produced, when, how, where, and by whom. This work aimed to describe the stages of implementing PPC in a small clothing company, highlighting its importance and necessity. It was applied in a clothing microenterprise located in the city of Maringá-PR. For this study, a literature review was conducted, and data from the company were collected through visits and questionnaires applied to employees. The results indicated that the lack of planning contributes to delays in order delivery and timely acquisition of raw materials, among other issues. Based on the results, improvements were proposed to address the identified difficulties, such as the use of the Trello tool to organize production information, facilitate order tracking, standardization of processes to reduce rework, training of employees to equip them, and performance monitoring to identify areas that need adjustments and implement improvements as necessary.